Quantized Detector Networks The Theory of Observation - Jaroszkiewicz, George (Cambridge University Press, 2017)
Scientists have been debating the meaning of quantum mechanics for more than a century. This book for graduate students and researchers gets to the root of the problem: how the contextual nature of empirical truth and the laws of observation impact on our understanding of quantum physics. Bridging the gap between non-relativistic quantum mechanics and quantum field theory, this novel approach to quantum mechanics extends the standard formalism to cover the observer and their apparatus. The author demystifies some of the aspects of quantum mechanics that have traditionally been regarded as extraordinary, such as wave-particle duality and quantum superposition, emphasizing the scientific principles rather than the mathematical modelling. Including key experiments and worked examples throughout, the author encourages the reader to focus on empirically sound concepts and avoid metaphysical speculation.